A99 OPTIMIZING COLONOSCOPY PROCEDURES AND REDUCING PATIENT ANXIETY THROUGH RECENTLY DEVELOPED ONLINE INFORMATION RESOURCES. (4th March 2021) - Jain, A; Jain, R; Nugent, Z; Davidson, D; Solati, Z; Restall, G; Reynolds, K; Shafer, L; Singh, H
Abstract: Background: Invasive medical procedures such as colonoscopies are known to cause psychological distress and anxiety. Patient anxiety leads to reduce patient compliance for colonoscopy and increased adverse effects. Patient education prior to colonoscopy has previously been shown to have positive effects on outcomes and experience. Based on patient and provider input, we have developed easy to read written materials and easy to follow video materials, which other patients have rated highly. These, along with other materials, are embedded on Mycolonoscopy.ca. Mycolonoscopy.ca is a website that provides online information access for patients regarding preparation and peri-procedural expectations. Information about accessing the website is provided with appointment materials (which includes information about split-dose versus one day bowel preparation, giving patients the option between the two) mailed to all patients undergoing outpatient colonoscopy in Winnipeg. Aims: (1) To evaluate the current use of mycolonoscopy.ca among patients undergoing colonoscopy (2) To determine whether there is an association between visitation to the website and patient outcomes such as reduction in procedural anxiety, bowel preparation tolerance/compliance, and bowel preparation score. Methods: A paper-based survey was given out to patients at their colonoscopy appointments. Univariate and multivariate logistic regression analyses was performed to determine the factors associated with website visitation and association with procedural anxiety, bowel preparation compliance and bowel preparation scores. Results: A total of 593 participants were given the surveys, of which 506 were completed. 17.4% of participants had visited the website prior to their colonoscopy. Visitors to mycolonoscopy.ca and those that had heard of the website were more likely to consume a split-dose bowel preparation (63.9% and 68.2% respectively) compared with non-visitors (52.5%) (p=0.0062). Individuals who consumed split-dose bowel preparation had a median Boston bowel preparation score of 9, compared with a score of 7 for individuals who used other forms of preparation (p<0.0001). 31.3% of website visitors were very or extremely worried about their colonoscopy compared with 17.9% of non-visitors. 76.6% of individuals agreed or strongly agreed that visiting the website helped them prepare for their colonoscopy and 69.7% who visited the website agreed or strongly agreed that it helped to reduce their stress/anxiety for the procedure as well. Conclusions: Our study suggests that use of an informative online platform such as mycolonoscopy.ca can help to improve patient education prior to colonoscopy, reduce anxiety and stress surrounding the procedure, and improve bowel preparation compliance and bowel cleansing score. Funding Agencies: CAG